2018
DOI: 10.1016/j.rmcr.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism and deep vein thrombosis secondary to idiopathic hypereosinophilic syndrome

Abstract: Acute pulmonary embolism (PE) is a most dangerous complication that needs prompt treatment to reduce potentially death. There are many well-known prognostic factors indicate the morbidity and mortality in various thromboembolic events. Persistent eosinophilia in peripheral blood can lead to tissue infiltration and even organ damage, but the urgent event of thromboembolism in pulmonary provoked by eosinophil eosinophilia in idiopathic hypereosinophilic syndrome (HES) is relative an unusual presentation. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Recently, gastrointestinal involvement was also recognized as the one and only poor prognostic factor in PAN (15). Another study of systemic necrotizing vasculitis with surgical abdomen found that eosinophilia was reported in 0 of 12 PAN cases, in marked contrast to its observation in all 4 cases of EGPA (10). To our knowledge, marked eosinophilia in gastrointestinal PAN, as seen in our case, has not been reported, and only one case of HES with necrotizing vasculitis in the skin and the small intestine, resulting in bowel perforation, has been reported (2).…”
Section: Discussionmentioning
confidence: 94%
“…Recently, gastrointestinal involvement was also recognized as the one and only poor prognostic factor in PAN (15). Another study of systemic necrotizing vasculitis with surgical abdomen found that eosinophilia was reported in 0 of 12 PAN cases, in marked contrast to its observation in all 4 cases of EGPA (10). To our knowledge, marked eosinophilia in gastrointestinal PAN, as seen in our case, has not been reported, and only one case of HES with necrotizing vasculitis in the skin and the small intestine, resulting in bowel perforation, has been reported (2).…”
Section: Discussionmentioning
confidence: 94%
“…Usually, skin symptoms such as urticaria or eczema or digestive symptoms such as nausea, vomiting, and diarrhea or respiratory symptoms such as asthma are the most common symptoms described by patients, but thromboses are not rare, comprising 20% or more of affected patients. 5,6 These symptoms may also be present in clonal eosinophilia and may be associated with peripheral nervous dysfunctions or thromboembolic complications. 8 Venous thromboembolism is the one of the most commonly described thromboses in hypereosinophilia and it may influence long-term treatment and prognosis of hypereosinophilic patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Venous thromboembolism is the one of the most commonly described thromboses in hypereosinophilia and it may influence long-term treatment and prognosis of hypereosinophilic patients. 5,6 Several pathophysiological mechanisms have been described in the last decades to explain the hypercoagulable state induced by hypereosinophilia that may lead to thrombosis. Of course the most commonly known has been related to chronic inflammation as in the Churg-Strauss vasculitis that may cause a real thromboangiitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the rarity and nonspecific clinical features of IHE/HES, available data on thromboembolism in patients with these disorders are limited and sporadic. Information on the clinical features and outcomes of these conditions is also limited 11 . To better understand the thromboembolic complications of HE, this case series summarises the patient demographics, clinical features, and short-term clinical outcomes in patients with IHE/ HES and concurrent VTE.…”
mentioning
confidence: 99%